What happens when ants fail at plant defence? Cordia nodosa dynamically adjusts its investment in both direct and indirect resistance traits in response to herbivore damage. (17th December 2012) - Frederickson, Megan E.; Ravenscraft, Alison; Arcila Hernández, Lina M.; Booth, Gregory; Astudillo, Viviana; Miller, Gabriel A.
Summary: Ants provide variable protection against herbivores to ant‐plants (i.e. myrmecophytes and myrmecophiles). The ways in which ant‐plants dynamically adjust both their direct (chemical and physical) and indirect (biotic) defences in response to varying levels of herbivory are not well understood. We experimentally generated a broad range of ant‐attendance levels and herbivory pressures in a tropical myrmecophyte, Cordia nodosa, which allowed exploration of the inducibility of and interactions between direct and indirect resistance traits. In response to increased herbivory, host plants encouraged indirect (biotic) defence by increasing domatium volume, regardless of whether ants were present on the plant. When ants were present, larger domatia housed more workers, which in turn decreased herbivory on adjacent leaves. Independent of the presence of ants, plants responded to increased herbivory by inducing both chemical (phenolics) and structural (leaf toughness, trichomes) resistance traits; these traits were associated with reduced palatability to a folivorous beetle. Synthesis. Our results show that both direct and indirect defences are inducible in C. nodosa, which suggests that C. nodosa may retain direct defences as insurance against varying levels of protection from its ant bodyguards. Thus, the predictions of optimal defence theory are not violated: although C. nodosa invests in multiple forms of defence, they are not redundant. Abstract : How do ant‐plants cope with the vagaries of biotic defenders? We found that the ant‐plant Cordia nodosa induces both direct and indirect defenses when ants fail to adequately to defend it against herbivory. Our results suggest that C. nodosa retains direct defenses as insurance against varying levels of protection from its ant bodyguards.